A Novel Nickel Pincer Complex in the Active Site of Lactate Racemase. Issue 1 (4th November 2015) - Xu, Tao; Bauer, Gerald; Hu, Xile
Abstract : Put through the pincer : A recent study revealed the structure of the Ni‐containing active site of lactate racemase. The Ni is coordinated by a SCS pincer ligand derived from a nicotinic acid mononucleotide.